Aplicación del material didáctico en el proceso enseñanza – aprendizaje, en el bloque curricular 5 “nuestra independencia”, en el área de estudios sociales en los niños y niñas de sexto grado de educación general básica de la escuela de educación básica “Filomena Mora de Carrión”, de la ciudad de Loja, año lectivo 2013- 2014 - Ordóñez Aguilar, Jackeline Cecibel (2015)
This research work entitled"APPLICATION OF TEACHING MATERIALS IN TEACHING - LEARNING PROCESS IN BLOCK CURRICULUM 5" OUR INDEPENDENCE ", IN THE AREA OF SOCIAL STUDIES IN CHILDREN OF SIXTH GRADE BASIC GENERAL EDUCATION SCHOOL OF EDUCATION BASIC " FILOMENA MORA DE CARRION" CITY OF LOJA, SCHOOL YEAR 2013- 2014 ", is an exploratory, descriptive and comparative approach of the teaching - learning that takes place within the research institution; reason we worked with the following objective Apply teaching materials to enhance the teaching-learning process in the sixth grade students basic general education curriculum block 5 "Our independence" in the area of Social Studies School Basic Education "Filomena Mora Carrion" City of Loja, 2013- 2014 school year, which allowed me to verify whether the application of teaching materials helped improve the shortcomings that existed in the students in their learning. Comprehensive, analytical, synthetic, or proactive models, workshop and comprehensive evaluation method, the same that helped me to support my research, each of the methods are helpful for teachers, due to: the methods used allowing verify the effects work an issue with the application of teaching materials. Furthermore techniques and instruments such as the interview aimed at teachers and a survey of students was used; the population was taken into account was 25 students and a teacher, who gave us their cooperation to check each of the insolvencies that exist in the classroom. The main result was then obtained from the interpretation of results was that the minority of students do not know how to define the concept of teaching materials. Due to the above it was concluded that the application of teaching materials helps students be aware of the contents of block 5, promoting the quality of learning.